Nang talung: Studying shadow play and the experience of Thai young people - Setthee Boonchoo (2019)
© 2019 IEEE. This research studied the opinions and experiences of young people about shadow play ('Nang Talung') in Hatyai, Songkhla Province, in the southern region of Thailand. This project aimed to develop strategies for promoting shadow play amongst young people and to identify which media and shadow play genres are the best suited for adapting Nang Talung to their interests. At this research stage, 135 people between the ages of 18-22 were questioned. From those, half had less experience with shadow play. Contributions to the findings came from members of Prince of Songkla University and other educational institutions in Hatyai, as well as from the Vice President of the Shadow Play Society of Songkhla, who is a shadow player and advocate of shadow play in the community, seeking to preserve this tradition. The research tools employed include an online questionnaire, interviews, data analysis (percentage, average and standard deviation). The results of this research are as follows: 1) shadow play has become less popular, is hard to find, and has been replaced by new media; 2) local youth use the internet and smartphones in everyday life, and support the use of technology to promote shadow play; and 3) shadow players want to preserve the traditional shadow play artform, but acknowledge that digital technology would help to promote shadow play. The results of this research can lead to the new design and development of shadow play to be more contemporary to suit the lifestyle of the younger generation.